1870. Excess Antibiotic Duration in Patients Hospitalized for Pneumonia: A Multi-Hospital Cohort Study. (26th November 2018) - Vaughn, Valerie; Flanders, Scott; Chopra, Vineet; Conlon, Anna; Malani, Anurag; Thyagarajan, Rama; Hsaiky, Lama; Gandhi, Tejal
Abstract: Vaughn VM, Flanders SA, Chopra V, Conlon A, Malani A, Thyagarajan R, Hsaiky L and Gandhi T Background: Despite guidelines recommending patients with pneumonia receive the shortest effective duration of antibiotic therapy, patients continue to receive antibiotics for longer than necessary. Patterns and predictors of excess antibiotic duration are not well understood. Methods: Cohort study of patients hospitalized with community-acquired pneumonia (CAP) or healthcare-associated pneumonia (HCAP) between November 2015 and January 2018 at 48 hospitals participating in the Michigan Hospital Medicine Safety consortium. Adult, non-ICU, medical patients were included. Patients with concomitant infections, severe immunosuppression, or unusual pathogens were excluded. Detailed patient data, included duration of antibiotic treatment, were abstracted from the medical record. Appropriate duration was calculated for each patient based on time to clinical stability, organism, and comorbidities. Patient outcomes included mortality, readmission, length of stay, transfer to intensive care, and Clostridium difficile infection. Disease-, patient-, provider-, and hospital-factors associated with excess antibiotic duration and association of excess duration with patient outcomes were evaluated using multivariable generalized estimating equations models. Results: A total of 3, 776 patients were included in the final analysis (2, 706 with CAP; 1, 070 with HCAP). 69% (2, 586/3, 776) of patients received excess antibiotic duration (Figure 1). Antibiotics prescribed at hospital discharge accounted for 52% of total and 94% of excess antibiotic days. Factors associated with excess duration included: identification of bacterial pathogen (OR 1.9, 95% CI: 1.3, 2.8), more signs of pneumonia (OR 1.2, 95% CI: 1.1, 1.3 per sign), and uncomplicated CAP (OR 2.7 vs. HCAP). Comorbid heart failure was protective (OR 0.8, 95% CI: 0.6, 0.9). Hospitals varied widely with even the top performing hospital over-treating half of patients (Figure 2). There were no differences in any outcome for patients receiving excess vs. appropriate antibiotic duration. Conclusion: Most hospitalized patients with pneumonia receive an excess antibiotic duration. CAP and antibiotics prescribed at discharge are major sources of excess use and thus key targets for stewardship. Disclosures: All authors: No reported disclosures.